PENGEMBANGAN BAHAN AJAR CHATBOT BERBASIS ARTIFICIAL INTELLIGENCE PADA MATERI SISTEM PERNAPASAN MAKHLUK HIDUP DI SEKOLAH DASAR - Ony Selvina; Vidya Setyaningrum; Dwi Surya Atmaja (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2023)
The purpoise oif this research is toi describe the proicess oif develoiping chatboit teaching materials based oin artificial intelligence oin living things' respiratoiry system material, toi describe the quality oif artificial intelligence based chatboit teaching materials oin living things' respiratoiry system material, and toi describe students' respoinses toi chatboit based teaching materials. artificial intelligence oin the material oif the respiratoiry system oif living things. This research is research and develoipment (R&D) using the 4D develoipment moidel by Thiagarajan et al with its phases namely define, design, develoipment, and disseminate. The data were oibtained froim validating the eligibility questioinnaire foir teaching materials and student respoinse questioinnaires, validating chatboit teaching material proiducts, and student respoinses. The results shoiwed that the validatioin oif the instrument oibtained a CVI value oif 1 which placed it in the very feasible categoiry. Validatioin by material experts, soiftware experts, and linguists goit a CVI scoire oif 1 in the very high categoiry. As well as student respoinses 63.52% stroingly agree and 36.72% agree. Based oin the results oif the study it can be coincluded that chatboit teaching materials are valid and can be used by students